At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
the formula is a^2+b^2=c^2
Which one is the hypotnus? the longest side?
rigth i'm using that formula but my answers are coming up negative? :-(
are you trying to solve for m?
yes slove for m
i got negative 5 and 1 and then i time them numbers by the giving number and they are still negative
\[(5m) + (3m)^2 = (2m+ 6)^2\]
woops forgot a squared
(5m)^2 + (3m)^2 = (2m + 6)^2 m = -0.76619 or m = 1.56619 But m = -0.76619 is an extraneous solution, so m = 1.56619 Consequently, the sides are about 7.83, 4.70, and 9.13
\[(5m)^2 + (3m)^2 = (2m+6)^2\]
Romero correct....dinosaur that looks correct how you come up with that answer?
You have a quadratic so you can have two values for m
if square all the numbers you get\[25^2 + 9m^2= 4m^2 + 24m+ 36\] get everything to one side you have \[30m^2 - 24m -36 = 0\]
where a = 30 b =-24 c=-36 and you use the quadratic formula to find the answers. Do you know to do from now on?
Romero that is what i got too and at the end the number are not coming out as whole numbers
Does the question say anything about what side is the longest? or m belongs to some interval?
the picture shows 5m to be the longest side
lol wow then we have it wrong
I thought so, because that would make the answer look nicer :)
if 5m is the longest side, then: \[(5m)^2=(3m)^2+(2m+6)^2 \implies 25m^2=9m^2+4m^2+24m+36\] \[\implies 12m^2-24m-36=0 \implies m^2-2m-3=0\] then after factorization: \[(m-3)(m+1)=0 \implies m=3, m=-1\]
since the value of m represents length, we only take the positive value, that's m=3.
awww thanks that look like that might be answer your a lifesaver :-)
then your sides are: 5m=15, 3m=9 and 2m+6=12
You're welcome :)